Local and foreign tourists' image of highland tourism destinations in Peninsular Malaysia - Aziz, Azlizam; Zainol, Nurul Amirah (Universiti Putra Malaysia Press, 2009)
This study was conducted with the purpose of identifying and comparing the images of highland destinations in Malaysia, held by both local and foreign tourists. Data from 897 respondents, comprising of both local and foreign tourists who had visited the three highlands (Cameron Highlands, Fraser’s Hill and Genting Highlands), were collected using a stratified random sampling technique through a questionnaire survey. Forty-one destination attributes were included in the factors, which were analysed and compared between the local and foreign tourists, using the Independent-sample T-test. Based on the results, six image factors were identified for the highland destinations, and these were labelled as “accessibility and services”, “local attractions and facilities”, “general mood and vacation atmosphere”, “leisure and recreational activities”, “natural surroundings”, as well as “nature and family-oriented.” The present study also found significant difference in the images held by the local and foreign tourists for the factors on “accessibility and services”, “local attractions and facilities”, “leisure and recreational activities”, as well as “natural surroundings.” The findings suggested that the local tourists had a higher perceived image than the foreigners towards the highland destinations in Peninsular Malaysia. The findings of the study also provided theoretical and practical implications for the tourism authorities of Malaysia, particularly in enhancing the development of the tourism industry for the highland destinations.